Islamic Boarding School Management: A Comprehensive Analysis of a Special Program for Fostering Students' Disciplinary Character in Madrasah Ibtidaiyah - Hidayat, Wahyu; Hidayat, Nur (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This study investigates the role of Islamic Boarding School Management in fostering disciplined character among students at Madrasah Ibtidaiyah (MI) Al Ma'had An-Nur, utilizing a qualitative, descriptive approach. Data collection involved interviews, observations, and documentation, focusing on the disciplinary program's planning, implementation, and evaluation stages. The research highlights the Islamic Boarding School as a critical environment for continuous supervision and character development, embedding Quranic values in everyday life. The process involves three educational pillars: madrasah, family, and community, with learning experiences shaped through exemplary behavior and habituation. The study's findings show that at MI Al Ma'had An-Nur, disciplinary character development is executed through structured phases, incorporating goal setting, program implementation, continuous support, and rigorous evaluation. The school's approach integrates religious, educational, and communal elements, making it a powerful model for Islamic education. However, the study's focus on a single institution and reliance on qualitative data suggest broader research, including comparative studies and quantitative methods, to deepen understanding of Islamic Boarding School practices. The research serves as a reference for other Islamic schools in developing character development programs and contributes to the broader field of Islamic education.